Pesquisa participativa na avaliação de armadilhas e contole populacional de cosmopolites sordidus - Santos, Saint Clair Lira (Universidade Federal Rural do Semi-Árido, 2010)
The banana (Musa spp) is one of the most consumed fruits in the world. It constitutes an important food, because of their chemical composition and content in vitamins and minerals, especially potassium. It is notable for being versatile, by their taste, low price and their easily of being consumed in natura, favoring the poor population. There are several challenges to banana production in the world, including the aspect of food security, as regards not only the quantity produced, but also the quality of fruits, mainly under the aspect of demand for products free of pesticides. Focused in the perspective of agroecology theme, this study considered the involvement of local farmers, like experimenter farmers offering in their own work, not just a research environment, but also a demonstration unit for students and banana producers of these region. This research had as main objective of studying the population dynamic of C. sordidus traps and evaluate their control in terms of the Vale do Açu-RN. We will also collaborate with the technical support to local producers, since research has allowed him to these, during and after the experiments, as a way to achieve a participatory ownership of the results. It was observed population dynamic of adult C. sordidus, so that the population peak was in June 2010. As the larvae, it was found that two population peaks occurred in the month of December 2009 and in July 2010. The climatic variables did not influence the population dynamics of adults and produced negative effects in the young population of these insects, especially rainfall and relative humidity. There were differences between the traps studied on the capture efficiency of C. sordidus. Considering the four collections, economically, the best treatment was the "T4" Bait type "tile" (80 baits / ha), which had the lowest ratio of total cost and average of trapped insects. Considering eight samples, economically the best treatment was the "T1", Cosmolure ® Drum, which had the lowest ratio of Total Cost and Average of trapped insects. Treatment with bait type "roof" (T4) is greater sustainability for family farmers, not creating dependency on external inputs and on the other hand, provide occupation of manpower, thus contributing to income generation and environmental preservation .
Participatory research on evaluation of traps and Population control Cosmopolites sordidus
Keywords: Research participatory; Banana weevil; Ecological traps.; Pesquisa participativa; Moleque da bananeira; Armadilhas ecológicas; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA